Compound robust flight time and heading angle constrained guidance law. Issue 2 (2020) - Ji, Yi; Pei, Pei; Lin, Defu; Zhao, Jianting; Wang, Wei
Abstract: This work studies accurate interception problem for salvo-attack missions and proposes a robust guidance law in the presence of impact time and angle constraints. First, the dynamic model for planar homing endgame guidance is built. Different with conventional guidance dynamic model, this work takes the derivative with respect to range, rather than time. Next, the trajectory of desired line-of-sight is formed and a time-to-go prediction method is introduced. On this basis, according to sliding mode methodology, a sliding manifold consisting the knowledge of time-to-go and line-of-sight angle is built and an integrated Lyapunov control method based guidance law is deduced to force this sliding manifold converge to a small region around zero in finite time, so that the missile will intercept target with a desired flight time and a heading angle. Detailed theoretical analysis and numerical simulations verified above properties.